Situated sounds of place in three songs by Wilhelm Stenhammar: Interpreting sites in songs from an anniversary romansafton at Konserthuset, Stockholm (September 2021) - Lindskog, Annika (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2023)
Many art songs relate ideas of place as they express relationships to sites and interpret their meanings. The place-making they engage in might encompass physical geographies, narratives of place, or negotiations around experience of places and spaces, and explore aspects of spatiality, historicity and temporality. This article listens to three songs by Wilhelm Stenhammar and argues that their relationship – textually, musically, and performatively – to topographies, sites, and situated experiences of place makes them geographically connected. It suggests, with musical and cultural geographers Grimley, Hudson, Malpas a.o., that place is constructed from interactions, experiences and narratives, and attempts to demonstrate both how these place-relationships can be read in musical texts, and how those texts can be considered active agents in place-making and geo-cultural performativities. Keywords: place, art songs, Stenhammar, musical geography, cultural geography, Nordic